Bridging the cultural divide: Simulated patient encounters to enhance medical students’ cross-cultural competences – A pilot study - Aleksandra Walkowska; Piotr Przymuszała; Patrycja Marciniak-Stępak; Maria Nowosadko; Ewa Baum (PLoS ONE, 2025)
There is an increasing awareness of the need to include culture sensitive actions and knowledge in the medical curriculum to ensure quality care for the growing number of culturally and linguistically diverse patients in Polish healthcare system. However, the research on the availability and effectiveness of cultural training for Polish medical students still seems insufficient. This study was designed to evaluate the impact of a simulation-based learning intervention with simulated patients on medical students’ cross-cultural sensitivity, awareness and self-efficacy of their cross-cultural knowledge and skills as well as to collect participants’ opinions about the simulation-based learning experience. The pre-intervention and post-intervention questionnaires consisting of the validated Polish version of a 24-item Intercultural Sensitivity Scale and the self-developed questionnaires evaluating students’ self-efficacy of their abilities were used. Additionally, the post-intervention questionnaire was also used to collect general impressions from the training course. The questionnaires were answered by 70 students participating in a 15-hour cultural content module, including workshops and simulation sessions with simulated patients. Students’ intercultural sensitivity and self-efficacy regarding their cultural knowledge and skills improved significantly post-intervention. Students experienced the simulated encounters as authentic and useful in advancing their cultural understanding and cross-cultural communication skills. Coupled with appreciative students’ feedback, our analysis indicated that classes with simulated patients can serve as a reliable and effective learning method for enhancing cross-cultural competence of future doctors.